Preparation of Reed Straw-Based Panels Bonded by Soy-Based Adhesives: Optimization via Response Surface Methodology - Zhang Yingjie; Yong Wang; Wanli Lou; Dongbin Fan (Advances in Materials Science and Engineering)
The optimization of manufacturing conditions for reed straw-based particleboard by soy-based adhesive was performed through response surface methodology. The interactions of various conditions, including adhesive amount, hot-pressing temperature, and hot-pressing time on wet internal bonding strength were investigated. A 3-level-3-factor Box–Behnken design was used to test the optimal preparation conditions of reed straw particleboard. The polynomial regression model for manufacturing conditions had a very significant level (p<0.01). In addition, the determination coefficient (R2) and the adjust determination coefficient (R2) of this model were found to be 0.969 and 0.9292, respectively. The conditions optimized by the model were 25% of adhesive amount, 138°C of hot-pressing temperature, and 27 min of hot-pressing time. Under the optimal conditions, validation tests were performed, and the average value of parallel experiments was 0.17 ± 0.02 MPa. Moreover, the thickness swelling of water absorption after soaking and mechanical properties (MOE and MOR) of samples prepared under optimized conditions were further measured, which all met the requirement of Type P6 particleboard. It could provide an efficient method for massive production of reed straw particleboard.